Trends and news of the cholera epidemic in 1910 in Iraq A historical descriptive study of the newspaper Sada Babel as an example - Dr.Qassim abdal hadi Al-Azraqji (Journal of College of Education, 2024)
Sada Babel newspaper was considered one of the important civil newspapers during the Ottoman era, because it continued to be published until November 1914 on a regular basis, even if it witnessed interruptions, it continued to be published, and had it not been for the denial of its owner, it would have remained in publication until the end of the Ottoman era. Perhaps what gives it its importance is the publication of (260) A number and an average number each week, and the characteristic of continuity pushed us to Select the search tagged (Trends and news of the cholera epidemic in 1910 in Iraq  A historical escriptive study of the newspaper Sada Babel as an example), to follow the newspaper’s follow-up of the cholera epidemic that occurred on the twenty-third of September 1910, to learn about the news and trends of the newspaper regarding the epidemic, as well as its follow-up of the health reality, and its role in spreading health awareness, It published health reports on a weekly basis, broadcasting health awareness and government procedures, and they were collected to determine the number of infections that occurred in the country, which amounted to (620) infections and (256) deaths, or a rate of (41,015%), which is a large number.    It is noteworthy that the researcher highlighted the statistics on infection and death and prepared a table showing the infections and deaths, in addition to the fact that the newspaper shed light on the most important health and preventive measures regarding the epidemic.
Keywords: Sada Babel newspaper, cholera epidemic